ANTHROPOMETRIC CHARACTERISTICS AND BODY COMPOSITION IN KARATE ATHLETES (Fiep Bulletin - online, 2013)
The aim of this study was to evaluate the anthropometric measurements and record the somatotipológic profile in regional karatekas  in intending to describe their biotype. 20 male athletes practicing Shotokan Karate aged 27 ± (12.7) years and at different grade levels. Anthropometric variables measured were: body mass (kg), height (m), wingspan, body fat percentage by skinfold thickness and bioelectrical impedance (BIE). For the determination of the components of somatotypes (endomorph, mesomorph, ectomorph), was used the somatotype© software. And the Body Mass Index (BMI). The results showed that there is a greater tendency for meso - endomorph individuals, which corresponds to 16 of the 20 analyzed. The average values of endomorphy in our study were higher than in all karate athletes studies. The averages of ectomorphy in our study were very similar to those found in studies with the same modality. BMI values in our study were higher than all other studies founded. Athletes are close to the upper limit of the overweight range. The body fat percentage values measured by skinfold and BIE technique showed no statistically significant differences. We conclude that seems to be no predominance of ectomorph and endomorph biotype in elite a Karate Fighters. This would be the most common biotype after years of work and training. In our study, we could not identify it, probably due to heterogeneity of sample. The BIE seemed to be a good and quick application method with satisfactory results as accurate as skin folds, however, the use of only one method would not be indicated to determine the anthropometric karate athletes factors.More studies linking time practice and other anthropometric factors are needed to better ideal biotype understanding in karate fighters.
Keywords: karate; Somatotype; Anthropometry